Digital techniques for the representation of virtual tours of urban architectural heritage - Giovanni Mongiello; Cesare Vedoscia; Riccardo Tavolare; Domenico Riglietti (Disegnare con)
The study illustrates the creation of a mobile App usable, above all, by laypersons, to create a virtual tour of the historical architecture that is being visited. The evolution of the historical center’s representation for the enjoyment by a wider audience, especially young and tourist, must necessarily be conveyed through smartphones, of which the new generations have acquired the full potential. Thanks to increasingly powerful devices, which can process complex 3D rendering in real time, it is possible to create an experience for the knowledge of the place with a 360° virtual tour. With the implementation of this App, we had tried to give back to the user a digital model full of useful information for the knowledge of the architectural place, but above all as much as possible immersive and intuitive in terms of navigation, using the gesture that today are rooted in smartphone users. The analyzed issues are many, including the implementation of technology for the creation of virtual tours targeted in teaching and tourism, it’s possible use to preserve and make known altered or no longer existing environments. The case study focuses on the viability of the Old Town of Altamura (Ba), characterized by numerous dead-end widening areas, called Claustri. The study was focused on Claustro Tricarico which presents architectural values of the Middle Ages, typical of the Apulian territory. DOI: https://doi.org/10.20365/disegnarecon.21.2018.18